(3GdWH GdQhMGfjs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GdQGRi PcQ ebGdI YedJgG aj EUdGM GdCNdGb , SCdfjgG HYV ENhGfj HeOjfI GdSdGe CjGe ebGej aCeQfi GdGejQ CSYOg Gddg HEfTGA cJGH jMJhi Ydi Led gPG GdeYfi HZGjI GdGNJUGQ hGdEjLGR s
(3BNQgG (B:s
(3hEPG bO CJjfG Ydi bUOfG ai cJGHfG gPG , hHdZfG ZQVfG ajg , aEfG NGJehf cdGefG HGdTcQ dQHfG YR hLd , aGdMeO ddg hGgH cd fYeI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdWH (B- (3U (B27 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B147 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI jhSa HGTG GdNGdOi HGdbOS (B((3eLGejY (B4/1) s
Keywords: (3GdWHs